Spatial distribution and associated factors of measles vaccination among children aged 12-23 months in Ethiopia. A spatial and multilevel analysis - Getanew Aschalew Tesfa; Abel Desalegn Demeke; Samuel Hailegebreal; Endris Seid Amede; Habtamu Setegn Ngusie; Mequanint Nakachew Kasie; Binyam Tariku Seboka (Taylor & Francis Group, 2022)
Introduction In Ethiopia, measles continues to be the cause of a significant number of vaccine-preventable infant morbidity and mortality due to the low vaccination rate. However, understanding the geographical distribution of the measles-containing vaccine first dose (MCV1) and identifying associated factors is crucial to setting up appropriate interventions. This study aimed to explore the spatial distribution and associated factors of MCV1 coverage among children aged 12-23 months in Ethiopia using national representative data. Methods A cross-sectional study design using a two-stage stratified sampling technique was used. The analysis was performed using STATA 14.2, ArcGIS 10.8, and SaTScan version 9.6 software. To find significant related factors with measles vaccination, researchers used multilevel logistic regression. Results The prevalence of MCV1 in Ethiopia was 58.5%. A spatial variation of MCV1 coverage was observed across the study area. The most likely significant primary clusters with low MCV1 coverage were observed in Liben, Afder, Shebelle, Korahe, and Nogob zones of the Somali region; Bale and Guji zones of the Oromia region, and Gedeo and Sidama zones of the SNNPR. Rural areas, maternal primary education, secondary and above school education, Orthodox religion, Muslim religion, health facility delivery, and Afar region were significantly associated with MCV1 vaccination. Conclusion The overall MCV1 coverage in Ethiopia was low. Aside from the inadequate coverage, there was a geographical variation across the country. Low MCV1 coverage areas should be prioritized to improve vaccination efforts to control measles across the country.